TKI or TKI combined with PD-1 inhibitors as second-line treatment for HCC patients after sorafenib failure - Lei, Jin; Chen, Bowen; Song, Meiru; Zhang, Linzhi; Zhang, Xinfeng; Gao, Xiaoqiang; Li, Yinyin; Lu, Yinying; Zuo, Shi (Frontiers in Pharmacology, 2022)
Background: Tyrosine kinase inhibitors (TKI) in combination with programmed cell death-1 (PD-1) inhibitors become the potential treatment modality for patients undergoing unresectable hepatocellular carcinoma (uHCC) in the first-line setting. However, the efficacy and safety of this combination regimen in patients after sorafenib failure remains unclear. Methods: Participants in this study included patients with uHCC after sorafenib failure who received TKI monotherapy (TKI group) or TKI combined with PD-1 inhibitors therapy (combination group) in our center from July 2018 to July 2021. The overall survival (OS) was used to be the primary efficacy endpoint, while progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR) were applied to be secondary endpoints. In addition, the adverse events are recorded and evaluated. Results: Among the 92 patients contained in this work, 50 patients were categorized into the TKI group, while 42 patients were in the combination group. There existed no evident differences between the two groups concerning the ORR (8.0% vs. 9.5%, p = 1.000). However, the DCR in the combined group was better in relative to that in the TKI group (71.4% vs. 50.0%, p = 0.037). In comparison with the TKI group, it was found that the combination group presented notably better median PFS (8.1 months vs. 4.7 months, p = 0.005) and median OS (21.9 months vs. 16.6 months, p = 0.042). According to multivariate analysis, PFS (HR 0.5, 95% CI: 0.3–0.8, p = 0.005) and OS (HR 0.5, 95% CI: 0.3–1.0, p = 0.051) were improved in the combination group in relative to the TKI group after the adjustment for some risk factors. Additionally, the incidence rates of grade ≥1 adverse event in the TKI group and the combination group were 96.0% and 97.6%, respectively. The most normal adverse event in the TKI group was neutropenia (n = 24,48.0%) and the combination group was hypoalbuminemia (n = 23,54.8%). All of these adverse events improved after symptomatic treatment, and no new toxic events were found to occur. Conclusion: TKI combined with PD-1 inhibitors showed better prognosis with manageable toxicity in uHCC patients after sorafenib failure compared with TKI monotherapy.